A ótica capitalista e o caso da lagoa Jacuném : descompassos nas intrincadas relações entre as realidades físicas e as funcionais dos espaços - Silva, Rose Marie Del Fiume (2014)
The relationship between man-nature has become tortuous over the years. The relentless pursuit of profit and accumulation of capital has corrupted the harmonious interaction between society and environment, leading to the depletion of its resources. The a